Export and Labor Market Outcomes: A Supply Chain Perspective - Evidence from Vietnam - Deeksha Kokas; Gladys Lopez-Acevedo; Ha Vu (Institute of Labor Economics (IZA), 2023)
Are the labor market changes from exports specific to exporting industries, or do they dissipate throughout the economy? To analyze this question, we study the case of Vietnam. Vietnam exported a total of 356B, making it the number 18 exporter in the world in 2021. Recent studies show provinces in Vietnam with greater exposure to tariff reductions observe greater rates of poverty decline and gains in wages and employment. We extend this literature by estimating the impact of exports propagated through domestic production linkages in Vietnam between 2010 and 2019. We find that direct exposure to exports has a limited impact, except for wages. When considering supply chain linkages, the impact on wages and income is more significant, especially for those in foreign sector and in the lowest income bracket. College premium decreases, and the gender wage gap narrows. With respect to employment variables, direct exposure to exports leads to increased employment and reduced inactivity and these findings remain consistent when accounting for supply chain linkages. The gains in employment are concentrated in workers with no schooling, while employment rate falls for more skilled workers.
Keywords: F16; J16; O19; 330; inequality; labor markets; international trade; poverty; jobs